The impact of sowing dates and seeding rates on the yield and grain quality of winter bread wheat under climate change conditions in the Northern Steppe of Ukraine - Barabolia, O.; Yanovskyi, R. (Scientific Progress & Innovations, 2025)
Winter bread wheat is one of the key grain crops, ensuring food security and economic stability in many countries. The high yield and grain quality of this crop are crucial for the food industry and its export potential. These characteristics are formed under the influence of multiple factors, among which sowing dates, seeding rates, and weather conditions play a significant role. This study aims to determine the impact of sowing dates and seeding rates on the yield and grain quality indicators of winter soft wheat under climate change conditions. The research was conducted from 2022 to 2024 in the agro-climatic conditions of the Northern Steppe of Ukraine. The study is focused on Ukrainian-bred winter soft wheat varieties: Perepilka Odeska, Mudrist Odeska, and Shchedrist Odeska. The analysis of climatic conditions revealed their variability, which significantly influenced the organogenesis of winter wheat. In 2024, the spring-summer temperature gradient, combined with insufficient moisture, was a particularly critical factor. Under more favorable weather conditions in 2023, the grain yield of all studied varieties was higher than in 2024, reaching a maximum of 9.85–9.92 t ha⁻¹ with sowing on September 10 at a seeding rate of 3 million seeds/ha. The tillering coefficient of plants in 2023 was higher due to better moisture availability during the spring period, whereas in 2024, the increased average monthly temperatures and low precipitation in April and May led to a reduction in the tillering coefficient by 0.1–0.4 units compared to the previous year. It was found that the most favorable sowing dates for achieving an optimal tillering coefficient were September 20 (seeding rate of 4 million seeds/ha) and September 10 (3 million seeds ha⁻¹). The number of productive stems remained relatively stable across both years, ranging between 8.0–8.8 million/ha at optimal sowing dates (September 10–20). Grain moisture during the study years was within the standard range (10.2–11.8 %) but decreased from early to later sowing dates while increasing with higher seeding rates. The test weight of the grain did not show significant changes due to weather conditions, remaining within 735–782 g L⁻¹, but was influenced by sowing dates and seeding rates. The highest test weight was observed for August 15 sowing with a seeding rate of 1 million seeds/ha (≥775 g L⁻¹, Grade 1 grain) and September 30 with 5 million seeds/ha (750–775 g L⁻¹, Grade 2 grain). The thousand-kernel weight remained relatively stable, fluctuating between 33–42 g, and decreased as the seeding rate increased.